Hexavalent Chromium Removal from Solutions: Surface Efficacy and Characterizations of Three Iron Containing Minerals. Issue 10 (7th April 2014) - Baig, Shams Ali; Wang, Qian; Wang, Zhuoxing; Zhu, Jin; Lou, Zimo; Sheng, Tiantian; Xu, Xinhua
Abstract In the present study, coupled reduction–sorption of Cr(VI) using three iron containing minerals (magnetite, hematite, and pyrrhotite) in aqueous solutions was investigated as a function of solution pH, contact time, and particle size. Detailed characterizations were performed using Brunauer–Emmett–Teller (BET), environmental scanning electron microscopy, and X‐ray diffraction (XRD) techniques. Results demonstrated that over 99% of Cr(VI) removal was achieved just after 1 min of the reaction using pyrrhotite with particle size (100–200 mesh). In comparison, removal efficiency of hematite and magnetite against Cr(VI) was below 40% after 2 h of the reaction. Acidic aqueous medium proved effective for Cr(VI) removal and nearly 100% Cr(VI) removal was achieved at pH 3 using pyrrhotite (30–40 mesh), while the surface efficacy of hematite and magnetite has also improved in acidic solution. In terms of removal efficiency, the three minerals followed the order: pyrrhotite > magnetite > hematite. However, no significant difference in the BET specific surface area was recorded among these minerals, but the mineralogical compositions played an important role for removing Cr(VI) in aqueous solutions. Analysis of XRD pattern revealed that iron contents produce Fe3FeSiO4(OH)5 and FeCr2O4 after the reaction with soluble Cr(VI) and precipitated. This study suggested that high ferrous ions‐based minerals can effectively remove Cr(VI) from contaminated water environments.